2018
DOI: 10.3390/c4030050
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach of Fabricating Graphene Nanoplates@Natural Rubber Latex Composite and Its Characteristics and Mechanical Properties

Abstract: Graphene has been demonstrated to be one of the most promising candidates to use as filler to improve the electrical, thermal, chemical and mechanical properties of natural rubber due to exceptional high surface area, superior electrical and thermal conductivity, and remarkable gas impermeability resistance. In this study, graphene nanoplates (GNPs) were mass-produced by a one-step chemical exfoliation of natural graphite and used as a filler for the fabrication of GNPs@natural rubber composite by a simple mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…58 The increase trend observed in the shore hardness with increasing both types of GNPs content also indicates that the surface of the nanocomposites become more homogeneous and harder. The increase in shore hardness can also be due to the flexibility of the GNPs in the polymer matrix as explained by La et al 50 Amine-GNPs is seen to be more effective with the recycled nylon blend when compared to the O2 functionalisation. This suggests a dependency on the type of functionalisation.…”
Section: Shore Hardnessmentioning
confidence: 85%
See 1 more Smart Citation
“…58 The increase trend observed in the shore hardness with increasing both types of GNPs content also indicates that the surface of the nanocomposites become more homogeneous and harder. The increase in shore hardness can also be due to the flexibility of the GNPs in the polymer matrix as explained by La et al 50 Amine-GNPs is seen to be more effective with the recycled nylon blend when compared to the O2 functionalisation. This suggests a dependency on the type of functionalisation.…”
Section: Shore Hardnessmentioning
confidence: 85%
“…Previous work on assessing the shore hardness of polymer composites reported slight increase which was attributed to the high surface area and dispersion of the reinforcement phase. [48][49][50] Incorporating GNPs in polymeric materials have been seen to lead to an increase 35,51,52 and reduction 45,[53][54][55] in tensile properties. Yesildag et al 52 reported a 20% increase in tensile modulus when 1 wt% GNPs was added to PA6.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the Halpin-Tsai model [97] to the storage modulus at 10 °C of the GE/NR composites allows the authors to deduce a shape factor of 719 thus suggesting a molecular level dispersion of GE in the elastomeric matrix. Most recently, La et al [98] have used a one-step approach for the mass production of graphene nanoplatelets (GNPs) by direct chemical exfoliation of natural graphite. The elongation at break and tensile strength are seen to increase upon addition of 0.3 phr of GNPS then decrease at higher loadings.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…While up to 706% rise in wPU tensile strength was reportedly obtained in a previous study by Hu and Zhang at 2% mass loading of rGO [220]. In addition, recent study by La et al noted about 10 fold increase in abrasion resistance, as well as ~400%, 200% and 30% increase respectively for elongation to failure, tear strength and tensile strength of GNP/NRL composite [240]. However, it is worth noting that majority of the results obtained so far (using GO and rGO) were largely achieved through emulsion mixing or in-situ polymerisation.…”
Section: Mechanical Propertiesmentioning
confidence: 71%